2016
DOI: 10.1080/15389588.2016.1171857
|View full text |Cite
|
Sign up to set email alerts
|

Estimating young novice drivers' compliance with graduated driver licensing restrictions: A novel approach

Abstract: Objective Current methods of estimating compliance with Graduated Driver Licensing (GDL) restrictions among young drivers with intermediate driver’s licenses—which include surveys, direct observations, and naturalistic studies—cannot sufficiently answer many critical foundational questions: What is the extent of non-compliance among the population of young intermediate drivers? How does compliance change over the course of licensure? How does compliance differ by driver subgroup and in certain driving environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…This is supported by research conducted in the United Kingdom, which indicates that those young drivers who commit ordinary violations such as speeding and close following in the first few months of their solo driving career were more likely to continue to commit these types of offences in higher numbers as they continued to drive for the first three years (Roman, Poulter, Barker, McKenna & Rowe, 2015). In New Jersey, USA, approximately 8 per cent of intermediate drivers were not compliant with passenger restrictions (Curry, 2017) and approximately three per cent were not compliant with night driving restriction (Curry, Pfeiffer & Elliott, 2017).…”
Section: Novice Driver Offendingmentioning
confidence: 77%
“…This is supported by research conducted in the United Kingdom, which indicates that those young drivers who commit ordinary violations such as speeding and close following in the first few months of their solo driving career were more likely to continue to commit these types of offences in higher numbers as they continued to drive for the first three years (Roman, Poulter, Barker, McKenna & Rowe, 2015). In New Jersey, USA, approximately 8 per cent of intermediate drivers were not compliant with passenger restrictions (Curry, 2017) and approximately three per cent were not compliant with night driving restriction (Curry, Pfeiffer & Elliott, 2017).…”
Section: Novice Driver Offendingmentioning
confidence: 77%
“…These studies have provided mostly high-level per-driver estimates, which have varied widely by jurisdiction and for several reasons may overestimate the true extent of non-compliance. 6,26 For example, a survey conducted in 2012 found that approximately 45% of NJ intermediate drivers reported driving with more than one passenger other than a family member. 27 Conversely, the QIE and naturalistic methods both estimate trip-level instead of driver-level compliance.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a series of previous papers, we demonstrated that this assumption is valid for the population of young intermediate drivers in NJ and that compliance with passenger and nighttime restrictions can be estimated using the QIE method. 11,14,19 Using these previously established methods, we identified all non-responsible 17-to 20-year-old intermediate drivers who were involved in a clean crash involving at least two vehicles from May 1, 2008 through April 30, 2012. For each study month, the prevalence of trip-level noncompliance was estimated as I i / N , where i is the restriction of interest, N is the total number of non-responsible intermediate drivers involved in clean multi-vehicle crashes, and I i is the number of these non-responsible intermediate drivers who were not in compliance with restriction i at the time of their crash.…”
Section: Methodsmentioning
confidence: 99%
“…12 However, surveys likely overestimate the true extent of young road users’ noncompliance as they reduce what is theoretically a continuous measure—the proportion of miles or trips in which a driver did not comply—into a categorical (e.g., ever: yes/no) or ordinal (e.g., how often: Likert scale) variable. 14 Additionally, low response rates may have limited representativeness and generalizability. Finally, the study reported that drivers’ awareness of the new GDL requirements increased in the post-decal period, increasing the potential that response-shift bias may have influenced pre-post survey compliance estimates.…”
mentioning
confidence: 99%